Leksikon Fauna dalam Pantun Atui: Kajian Ekolinguistik - alvi puspita (Balai Bahasa Provinsi Riau, 2024)
This research focuses on compiling the faunal lexicon contained in the Limo Koto pantun. The pantun sample taken was Pantun Atui. Knowledge of this fauna is important in the midst of an ever-changing nature and environment. The main theory used in this research is oral literature theory which is used to collect data and ecolinguistic theory to analyze the data that has been obtained. The data collection method in this research uses interviews, notes and recording methods. To analyze the data, descriptive analytical methods were used. The results of this research found 25 faunal lexicons in Pantun Atui. Based on the culture of the Kampar people as owners of pantun, the 23 fauna lexicons can be categorized into three types of lexicons, namely the Bawuo fauna lexicon, the Daghek fauna lexicon and the Kampau fauna lexicon. Meanwhile, there are 2 fauna lexicons that can be classified into marine fauna, namely swordfish and dolphins. These two marine fauna lexicons indicate that although Kampar is synonymous with rivers or kampau, it has connections with other sea-based areas.